(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article investigates the distinctive features of psychological operations (PSYOP) in the armed forces of the United States of America, France, the People’s Republic of China, and the Islamic Republic of Iran. Drawing on open-source doctrinal documents, academic research, and comparative military studies, the article analyses organisational structures, strategic objectives, methodological approaches, and technological capabilities that define each country’s psychological warfare posture. The study reveals that, although all four nations share the overarching goal of influencing the perceptions, attitudes, and behaviour of target audiences, their doctrines, institutional frameworks, and cultural underpinnings differ substantially. The findings are relevant for Uzbekistan’s ongoing modernisation of its defence sector and for researchers engaged in the comparative study of military psychology